2011
DOI: 10.4103/1119-3077.91745
|View full text |Cite
|
Sign up to set email alerts
|

Copper and selenium status of healthy pregnant women in Enugu, southeastern Nigeria

Abstract: High copper levels indicate that supplementation should not be undertaken during normal pregnancy. Dietary intake should be modified to ensure optimal selenium levels during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 34 publications
(36 reference statements)
6
18
1
Order By: Relevance
“…Furthermore, these authors revealed a slight tendency towards liver copper decrease in animals given selenium [19], which confirms the results of the current study. The negative relationship between selenium and copper is also supported by the study performed by Nwagha et al; they found that in the serum of pregnant women throughout the duration of pregnancy (1 st , 2 nd and 3 rd trimester), a selenium depletion was concomitant with an increase of copper [8].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, these authors revealed a slight tendency towards liver copper decrease in animals given selenium [19], which confirms the results of the current study. The negative relationship between selenium and copper is also supported by the study performed by Nwagha et al; they found that in the serum of pregnant women throughout the duration of pregnancy (1 st , 2 nd and 3 rd trimester), a selenium depletion was concomitant with an increase of copper [8].…”
Section: Discussionsupporting
confidence: 71%
“…Selenium supplementation has shown a protective action against toxic agents [7], although it is necessary to take proper precautions to avoid overdosing. On the other hand, its deficiency may result in various disturbances of the organism [8]. The issue of both lithium therapy and selenium supplementation is not a straightforward problem, since these elements show a narrow therapeutic range [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports of variations Table 1 in copper levels during pregnancy. While some studies reported increasing levels as pregnancy progressed, [43][44][45] others reported high prevalence of copper deficiency. [46,47] However, these studies did not take parity into consideration while making such assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals generally have been shown to be one of the most important groups of environmental pollutants having blood reference ranges that differ from country to country and from region to region due to geographical location, soil content, intake from diets and bioavailability (Nwagha et al 2011).…”
Section: Status Of Previous Pregnancy Complicationsmentioning
confidence: 99%